2021
DOI: 10.1080/10408444.2021.1965086
|View full text |Cite
|
Sign up to set email alerts
|

Does ozone inhalation cause adverse metabolic effects in humans? A systematic review

Abstract: We utilized a practical, transparent approach for systematically reviewing a chemical-specific evidence base. This approach was used for a case study of ozone inhalation exposure and adverse metabolic effects (overweight/obesity, Type 1 diabetes [T1D], Type 2 diabetes [T2D], and metabolic syndrome). We followed the basic principles of systematic review. Studies were defined as "Suitable" or "Supplemental." The evidence for Suitable studies was characterized as strong or weak. An overall causality judgment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 135 publications
(445 reference statements)
0
11
0
Order By: Relevance
“…Through comprehensive comparisons among studies we extracted, we found that the absence of adjustments for socioeconomic status may be a major contributor to these discrepancies. A systematic review on the risk of ozone inhalation and adverse metabolic effects concluded that the current evidence is insufficient to conclude whether ozone exposure causes T1D and is insufficient or suggestive for the association with T2D [ 28 ]. As a result, more evidence is needed to explore these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Through comprehensive comparisons among studies we extracted, we found that the absence of adjustments for socioeconomic status may be a major contributor to these discrepancies. A systematic review on the risk of ozone inhalation and adverse metabolic effects concluded that the current evidence is insufficient to conclude whether ozone exposure causes T1D and is insufficient or suggestive for the association with T2D [ 28 ]. As a result, more evidence is needed to explore these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Like our findings, a 2019 meta-analysis concluded that the odds for T2D were 1.03 and 1.05 times higher for incremental increases of 10 µg/m 3 in PM 2.5 and NO 2 exposures, respectively 16 . Studies assessing the association between O 3 and diabetes are much more limited, and the direction of the observed associations is inconsistent and varies greatly depending on the model covariates 42 . For example, a longitudinal cohort of 13,548 individuals in China found a 5.7% increase in diabetes incidence hazard associated with a ten µg/m 3 increase in annual O 3 exposure 43 .…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent long-term studies did not find a significantly increased diabetes risk associated with O 3 exposure in multipollutant models accounting for particulate matter 44,45 and NO 2 44 exposures. Moreover, a 2021 review concluded that evidence on the association between O 3 exposure and diabetes is insufficient to infer causality 42 . Our study also showed inconclusive results, possibly related to residual confounding, exposure measurement error, or the complexities of simultaneously estimating the effects of multiple air pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…14 Evidence of ozone-induced alterations of lipid metabolites and glucose intolerance remains unclear based on the existing toxicology and epidemiology research. 15,16 Physical activity has a joint effect or interaction with air pollution, and according to recent research, activity intensity can lessen the adverse impact of pollutants. 17 Chemical pollutants, which can be categorized as synthetic chemicals, natural mixtures, heavy metals, and endocrine-disrupting chemicals, increase the risk of metabolic diseases and T2D.…”
Section: Humiditymentioning
confidence: 99%
“…A meta‐analysis suggested that 12.28% of the risk of MetS could be attributed to PM 2.5 µm or smaller 13 ; this influence could harm adolescents and children at increased concentrations 14 . Evidence of ozone‐induced alterations of lipid metabolites and glucose intolerance remains unclear based on the existing toxicology and epidemiology research 15,16 . Physical activity has a joint effect or interaction with air pollution, and according to recent research, activity intensity can lessen the adverse impact of pollutants 17 …”
Section: Cardiometabolic Disease‐related Factorsmentioning
confidence: 99%